(untitled) (Research, Society and Development, 2022)
Currently, hemangioma is determined by the proliferation of blood vessels, a benign vascular neoplasm. It can appear as a kind of bubble, with a color that varies from red to purple. It has a high incidence in the head, neck and oral cavity region, constantly affecting the tongue, cheek mucosa and lips. Patients report painful symptoms in some cases, have difficulty in speech and chewing and aesthetic impairment. The knowledge of this neoplasm is of great importance to the dentist to perform the proper management. Among the therapeutic means, sclerotherapy is one of the least invasive choices, it has been applied more frequently, as satisfactory clinical and aesthetic results are presented. Therefore, this work will report a clinical case of a patient with Hemangioma, in which the sclerotherapy protocol with 0.05g / ml monoethanolamine oleate will be performed as an alternative treatment, achieving complete lesion involution, and without recurrence after 12 months.